'Reconceptualising internationalisation through students' eyes': Findings from a biographical study of female, international doctoral students in an Irish University. Issue 2 (August 2021) - Moran, Lisa; Green, Lorraine; Warren, Simon
This paper presents findings from an Irish qualitative study of postgraduate, female, international students. It focuses on their narrations of internationalisation, in respect of events leading them to become international students, and their reflections on their academic, interpersonal and societal experiences in Ireland. International students are generally understudied and marginalised as metaphorical 'others' within global education policies, often being reduced to mere recruitment and financial targets and units of analysis. However, this study shows that international students transcend widespread but static assumptions about them being in academic and social deficit when transitioning to life in another country and negotiating new educational contexts. Significantly, our interviewees discursively positioned themselves in multifarious ways in relation to Irish higher education curricula, drawing on various discourses to define their internationalisation journeys. Although the sample size is small and confined to female postgraduates, our data suggests that university policies in Ireland and internationally largely overlook the multidimensionality of international doctoral students' experiences. In our conclusion, we tentatively suggest ways in which international students' academic and intercultural experiences could in the future be enriched, and how international students themselves could more fruitfully contribute to Irish higher education.